Prevalence of Lynch syndrome and Lynch-like syndrome among patients with colorectal cancer in a Japanese hospital-based population - Noriyasu Chika; Hidetaka Eguchi; Kensuke Kumamoto; Okihide Suzuki; Keiichiro Ishibashi; Tetsuhiko Tachikawa; Kiwamu Akagi; Jun‐ichi Tamaru; Yasushi Okazaki; Hideyuki Ishida (2016)
We investigated the prevalence of Lynch syndrome and Lynch-like syndrome among Japanese colorectal cancer patients, as there have been no credible data from Japan.Immunohistochemical analyses for mismatch repair proteins (MLH1, MSH2, MSH6 and PMS2) were carried out in surgically resected, formalin-fixed paraffin-embedded specimens obtained from 1,234 newly diagnosed colorectal cancer patients between March 2005 and April 2014. The presence/absence of the BRAF V600E mutation and hypermethylation of the MLH1 promoter was analyzed where necessary. Genetic testing was finally undertaken in patients suspected as having Lynch syndrome.By the universal screening approach with immunohistochemical analysis for mismatch repair proteins followed by analyses for the BRAF V600E mutation and MLH1 promoter methylation status, 11 (0.9%) of the 1,234 patients were identified as candidates for genetic testing. Out of the 11 patients, 9 (0.7%) were finally diagnosed as having Lynch syndrome; the responsible genes included MLH1 (n = 1), MSH2 (n = 4), EPCAM (n = 1) and MSH6 (n = 3). The remaining two patients (0.2%) were regarded as having Lynch-like syndrome, since biallelic somatic deletion of the relevant mismatch repair genes was detected in the absence of germline mismatch repair alterations. None of the cases was identified as having germline MLH1 epimutation.The prevalence of Lynch syndrome among all newly diagnosed cases of colorectal cancer in Japan is in the same range as that recently reported by studies in Western population. The prevalence of Lynch-like syndrome seems to be extremely low.